The songs of the Violated Vereda Wetlands in the nooks of brazilian savannah backlands - Vasconcelos, Vitor Vieira; Seingyai, Apinyapon (Revista Campo-Território, 2013)
This reportseeks to present the outcome of exchanges conducted within the event, Songs of Violated Vereda Wetlands (Veredas Violadas), the most recent celebration of the Sagarana Festival: Becoming Guimarães Rosa for the Backlands (como Rosa para o Sertão), 2 in November 2012.Topics for discussion included conceptual and cultural aspects, and public policies on the ecosystems of vereda wetlands. Special emphasis wasplaced on the perception of traditional populations living in the Brazilian Savannah hinterlands and their relationship to the Veredas, including the expression of traditional life in the work of João Guimarães Rosa3. A typology of the environmental impact on the ecosystems of veredas is presented, based on the regional etymology by which the peoples of the hinterlands interpret these impacts.